Peningkatan Hasil Belajar Siswa Menggunakan Media Herbarium Berbasis Inkuiri pada Materi Plantae Kelas X - Solikhah, Ulvatul Nurul; Pujiastutik, Hernik (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This research is based on the learning done by the teacher now giving more lectures so that it seems boring for the students. This resulted in the difficulty of students achieving the expected competence due to lack of trained to develop the critical thinking power of students in solving problems. o overcome these problems, it is necessary to improve learning by doing action research class (PTK) using Herbarim media based inquiry. This research is a Classroom Action Research (PTK). This research was conducted with 2 cycles, that is cycle I and cycle II. This research was conducted at MA Mambaul Ulum Dagan Paciran Lamongan Academic Year 2017/2018 with the subject of the research is the class X students of IPA with 30 students consisting of 19 male and 11 female students. The purpose of this study is to improve student learning outcomes MA Mambaul Ulum especially class X. Data collection techniques used are: observation, tests and questionnaires to determine the response of students to the media herbarium. The results obtained that the Improvement of Student Learning Results Using Inquiry-Based Herbarium Media On Plantae Material Class X can be done well, this can be seen from the results of the percentage of students' learning completeness from cycle I which reached 77% in cycle II increased to 90%. As for the students response to learning is 87% of students express agree or happy with the applied learning model. The conclusion of this research indicates that the use of Herbarium Media Based Inkuiri can improve student learning outcomes in the material Plantae class X MIPA MA Mambaul Ulum Dagan Paciran Lamongan Year Teaching 2017/2018.